Investment Opportunity Set and Dividend Policy: An Evidence in Indonesia Manufacturing Sector - Ifadah, Anna Zulfatul (Management Analysis Journal, 2021)
This study aims to examine whether the investment opportunity set affects the dividend policyof manufacturing companies in Indonesia. The study population is manufacturing companies listed on the IDX during the 2009-2018 period. The sampling technique was carried out using a purposive sampling method and obtained 140 samples. Data analysis in this study used descriptive analysis, the best panel data estimation model test, and linear regression analysis. The result of the model test show that the best panel data estimation model is the random effect. Hypothesis test result show that the investment opportunity set has a significant negtive effect on dividends for manufacturing companies.